2003
DOI: 10.1111/j.1365-2249.2003.02302.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in monocytic expression of aminopeptidase N/CD13 after major trauma

Abstract: SUMMARYHLA-DR expression on monocytes as marker for monocytic function is severely depressed after major trauma. The membrane enzyme aminopeptidase N/CD13 can trigger help in antigen processing by MHC class II molecules of antigen-presenting cells. We determined the simultaneous expression of HLA-DR and CD13 on peripheral blood monocytes of patients with major trauma (injury severity score of ≥ 16). 1 : 1 conjugates of phycoerythrin (PE)-to-monoclonal antibody were used in combination with QuantiBRITE TM PE be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
4
7
0
Order By: Relevance
“…these possibilities by molecular mapping and mutation of the CD13/TLR4 interacting domains to determine whether disrupting the interaction impacts endocytosis of TLR4 or MR as well as identifying other additional CD13-interacting proteins by proteomic analysis. In addition, we and others (27) find that CD13 expression levels are remarkably upregulated by inflammatory activation signals and tissue damage, supporting the notion that a high level of CD13 expression is important during the immune response. Understanding the contribution of these and other CD13-mediated mechanisms to endocytosis is the subject of active investigation in our laboratory.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…these possibilities by molecular mapping and mutation of the CD13/TLR4 interacting domains to determine whether disrupting the interaction impacts endocytosis of TLR4 or MR as well as identifying other additional CD13-interacting proteins by proteomic analysis. In addition, we and others (27) find that CD13 expression levels are remarkably upregulated by inflammatory activation signals and tissue damage, supporting the notion that a high level of CD13 expression is important during the immune response. Understanding the contribution of these and other CD13-mediated mechanisms to endocytosis is the subject of active investigation in our laboratory.…”
Section: Discussionsupporting
confidence: 87%
“…In an effort to uncover potential clues into the mechanism by which CD13 may regulate endocytosis in the context of infection or injury, we investigated the effect of inflammatory signals on CD13 itself. Previous studies had suggested that CD13 expression levels were increased in human peripheral blood monocytes in response to injury in vivo or LPS treatment in vitro (27). In agreement with this finding, we found that LPS stimulation of WT macrophages induced CD13 protein expression over 4-fold in a time-dependent manner (Fig.…”
Section: Cd13 Expression Is Upregulated In Response To Lps and Directsupporting
confidence: 92%
“…In an earlier study of polytrauma patients the observed decrease in monocytic HLA-DR expression was accompanied by a delayed strong increase of membrane peptidase APN/ CD13 expression (23). In the present study, we describe for the first time that the decrease in monocytic HLA-DR intensity is paralleled by an increase in APN/CD13 intensity in advanced RCC tumor stages.…”
Section: Discussionsupporting
confidence: 71%
“…Consistently, we also observed a significant increase in CD13 expression in 6-OHDA-lesioned animals that was reversed by PDGF-BB. CD13 levels are known to increase upon angiogenesis and inflammation (Di Matteo et al, 2011;Huschak et al, 2003). PDGF-BB may reduce the inflammation in the striatum and CD13 expression.…”
Section: Accepted Manuscriptmentioning
confidence: 99%